Aspek Biologi Sycanus annulicornis Dohrn. (Hemiptera: Reduviidae) Yang Dipelihara Dengan Pakan Alternatif Larva Alphitobius diaperinus Panzer (Coleoptera: Tenebrionidae) - Abdul Sahid (Mulawarman University, 2019)
Assassin Bug, Sycanus annulicornis Dohrn. (Hemiptera: Reduviidae) is one of the predatory polyphagous insects that has the potential to be used as a natural enemy in pest control in food crops, horticulture, plantations, and forestry plants. This study aimed to evaluate the biological aspects of S. annulicoris maintained with alternative feeds of Alphitobius larvae diaperinus Panzer. The results showed that S. annulicornis maintained with A. diaperinus larvae produced an egg incubation period of 19.0 ± 2.1 days, fecundity of 88.1 ± 46.0 eggs, fertility of 41.8 ± 11.4%, time of development of nymphs 82.4 ± 6.4 days, mortality of nymphs 53.5 ± 3.3%, duration of male and female imago: 36.3 ± 12.8 and 61.1 ± 18.1 days, male sex ratio: female 1: 4, and the male and female S. annulicornis imago life cycle: 118.7 ± 9.6 and 143.5 ± 12.3 days. The results showed that A. diaperinus larvae could be used as an alternative feed for mass propagation of S. annulicornis in an integrated pest control program.